Does consanguinity increase the risk of mental ilnesses? A population-based study. Issue 2 (2nd April 2016) - Bener, Abdulbari; Abou-Saleh, Mohammed T.; Mohammad, Ramzi M.; Dafeeah, Elnour E.; Ventriglio, Antonio; Bhugra, Dinesh
ABSTRACT: Over the past few years, there have been many encouraging advances identifying genetic risk factors in mental illnesses. Psychiatric disorders have been recognised as carrying the biggest burden of disease worldwide. This is reflected in the State of Qatar where two of the top three burdens of disease are mental disorders. We set out to study the burden of commonest psychiatric disorders among consanguineous marriages at Primary Health Care Centres (PHCs) using the World Health Organisation Composite International Diagnostic Interview (WHO-CIDI) and examine their symptom patterns and co-morbidity in Qatar. A prospective cross-sectional study was carried out over one year between November 2011 and October 2012. A total of 2000 Qatari subjects aged 18 to 65 years were approached; 1475 (73.3%) gave consent and participated in this study. Prevalence of psychiatric disorders using the WHO-CIDI, version 3.0, showed that six most common disorders were major depression disorders (18.3%), any impulse control condition (18.3%), any anxiety disorders (17.2%), any mood disorders (16.9%), followed by separation anxiety disorders (15.2%), and personality disorder (14.1%). The mean age ± SD of the 1475 subjects interviewed was 39.3 ± 9.8 years. The rate of consanguinity in the present generation was 31.5% (95%CI = 29.1–33.7). There were statistically significant differences between consanguineous and non-consanguineous with regards to age, educational status, occupation status and household income, as well as body mass index, cigarette smoking and sheesha (water pipe) smoking. Statistically significant differences were also found related to lifestyle habits between consanguineous and non-consanguineous marriages. One-fifth of all adults who attended the PHC Centre 20% had at least one psychiatric diagnosis. The prevalence of generalized anxiety disorders – social phobia, specific phobia, major depression and personality disorders – was significantly higher in consanguineous marriages than in non-consanguineous marrages. Thus any prevalence should be measured according to consanguineous marriages.